REPRESENTATION OF KERIS MARRIAGE IN NEW MEDIA: CRITICAL DISCOURSE ANALYSIS - I Made Dwi Gunarta; Ni Luh Manik Puja Dewi , (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
The cultural practice of kawin keris reflects gender inequality within Balinese society. This phenomenon is not limited to real-life practices but also becomes the subject of contested discourses in new media. The representations and identities emerging in digital spaces highlight an issue that deserves critical academic attention. This study focuses on how the cultural practice of kawin keris is represented in new media and what dominant discourses shape its construction of reality. The research applies Stuart Hall’s theories of representation and identity as its theoretical framework. A qualitative approach using critical discourse analysis was employed to examine digital media content, supported by observation, interviews, and literature review. The findings reveal three main positions in the representation of kawin keris. First, the dominant-hegemonic reading legitimizes the practice as a solution to unresolved marital problems. Second, the negotiated position reflects audiences who mediate between acknowledging gender injustice and offering alternative solutions. Third, the oppositional position rejects the practice outright, framing it as a form of symbolic violence and gender-based injustice. These varied representations demonstrate the contested cultural meanings of kawin keris within the dynamic space of new media.